Performance of Contrarian Investing for Shariah Compliant Stock Portfolio - Abd Halim, N.N.; Jusoh,N.; Elias,S.M.; Karmila Hanim Kamil (Universiti Sains Islam Malaysia, 2024)
Contrarian strategy is applied in the stock market by buying past losers and selling past winners. In this study, the profitability of contrarian strategy on Shariah compliant stock is explored for Malaysian stock market and the application is targeted for individual investors. Monthly closing price of 50 Shariah Compliant individual stock from January 2012 to December 2016 are utilized in this study. Shariah compliant individual stock portfolios based on contrarian strategy are constructed and the performance of the developed portfolio are measured. This study utilizes three ranking and holding period strategy which are the 12/12 strategy, 12/6 strategy and 6/6 strategy. The results indicate that contrarian investment strategy is profitable in Malaysian market using short-term ranking and holding period which is the 6/6 strategy. The return generated is 3.42% as compared to market benchmark of 2.78% for the same period. Thus, the strategy beats the market benchmark by 0.64%. Furthermore, this strategy gives the highest return per unit of risk taken by investors as measured by the portfolio volatility. This means that shortterm contrarian strategies may provide abnormal returns for Shariah compliant investors.